ANALISIS SISTEM PENGENDALIAN INTERNAL DAN RISIKO DALAM SIKLUS PENGGAJIAN KARYAWAN MENGGUNAKAN PENDEKATAN COSO - Iradhati Salsabila; Ludovicus Sensi Wondabio (ITB AAS Indonesia Surakarta, 2023)
The purpose of this study was to analyze the internal control system conditions of Hospital X on the payroll cycle using COSO control principles and to identify the application of COSO Enterprise Risk Management on Hospital X's payroll cycle. This study used primary data. The research approach used in this study is a qualitative approach. This research method uses Internal Control Questioniomatres, interviews and documentation. In this study, the questionnaire used was specific in the form of an internal control questionnaire. The instruments used in this internal control questionnaire were developed based on COSO's internal control components which consist of seventeen existing principles. The results of this study indicate that both in terms of planning and implementation of internal control at Hospital X is quite good. The policies issued are complete enough as a basic reference, especially for the clinical field of hospitals. However, in the payroll cycle itself, internal control has not gone well. This is indicated by the absence of specific policies made as a reference for the implementation of internal control over the payroll cycle, especially for the two divisions that directly supervise the payroll process, namely the HR department and the finance department. Likewise with the risk management of hospital X. Hospital X has actively developed a risk register that is in accordance with the COSO framework. However, just like the internal control, the risk management payroll cycle has not been carried out.